Pharyngo-cutaneous fistula post total-laryngectomy: a local experience (2020)
Background: Pharyngo-cutaneous fistula is a major complication of total laryngectomy. Despite its significant impact on the patients' nutrition and management outcome, there is lack of consensus for recognising high-risk patients and factors associated with fistula formation. Hence, this study was aimed at determining the incidence of pharyngo-cutaneous fistula and factors associated with fistula formation. Methods: A retrospective collection of data on all cases of laryngeal cancer diagnosed histologically and had total laryngectomy, in the Otorhinolaryngology Department of a tertiary centre in Southwestern, Nigeria, from 2007 – 2016. The data collected include age, gender, tumour stage, tracheostomy, adjuvant therapy extent of laryngectomy procedure and factors for pharyngocutaneous fistula. Results: Forty-two patients had total laryngectomy, male to female ratio was 7.4:1 and mean age was 52.3 ± 2.1 years. All patients had pathological diagnosis of stage 3 (83.3%) and stage 4 (16.7%) laryngeal cancer, respectively. The incidence of pharyngo-cutaneous fistula was11.9% and the factors related to fistula formation were prior radiotherapy treatment and diabetes. Age, gender, neck dissection procedures, site of primary tumor and emergency tracheostomy did not contribute to fistula formation. Spontaneous fistula closure was achieved in all cases except one patient who had surgical closure. Conclusion: Pharyngo-cutaneous fistula formation post-surgery is related to the presence of co-morbidities. The high percentage of spontaneous closure underscores the need for a conservative management approach